Monitoring and evaluation practice to discern meaningful change in community-based early childhood development centres - Sikobi, Thembeka (Graduate School of Business, 2018)
After 23 years of democracy South Africa still faces poor education quality, a class-based education system and poor academic performance. These issues are exacerbated by South Africa’s apartheid history and perpetual inequality. Access to quality Early Childhood Education (ECD) is recognised as a solution that can improve education outcomes and overcome poverty and inequality in the country. However, challenges remain in the effective implementation of ECD programmes. This study seeks to investigate the quality of ECD centres in rural communities in order to gain a deeper understanding of the context in which they operate and be in a better position to inform public funding policies and investment decisions. The main research question asks how the quality of ECD that is delivered through community-based ECD centres can be improved either through the use of public funding other funding sources? Approaches to monitoring and evaluation (M&E) and impact considerations are examined in community settings. From this, theoretical and practical lessons are drawn to form the basis for analysis of the research findings. The study adopts a predominantly qualitative approach using interviews with parents and teachers, as well as observations and questionnaires. A total of 40 ECD centres were surveyed and 21 interviews conducted in KwaZulu-Natal (KZN) province in South Africa. The study areas are three rural communities, namely Vulamehlo, Izingolweni and Msinga. Based on quality definitions explored in this dissertation, the study finds that the need to improve the quality of ECD service delivery remains pertinent and that there is a gap in parental ECD knowledge and practice.